PENGUKURAN KINERJA KARYAWAN MENGGUNAKAN MOTIVASI KERJA DAN GAYA KEPEMIMPINAN PADA KOPERASI DI KABUPATEN LAMPUNG TIMUR - Suharto Suharto; Suwarto Suwarto; Evy Yustivia (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2022)
The purpose of this study was to determine the effect of Work Motivation and Leadership Style on Employee Performance in Koperasi District of East Lampung regency. Type of research is descriptive qualitative research procedures that produce descriptive data based on the results of a quantitative analysis of the variables of the study. The technique of collecting data using interviews, documentation and questionnaires using a questionnaire. The analysis tool used is to use data quality analysis and multiple linear regression analysis.The method used in this research is explanatory survey method . This type of research is quantitative research with the object of research is the Work Motivation , Leadership Style and Employee Performance. The study population is Source of Koperasi District of East Lampung district are 33 people with the number of samples taken as many as 30 customers were taken using techniques pourpisivesampling. Decision-making research results based on the results of the analysis using multiple linear regression analysis .In conclusion, the results of the analysis of motivation have a significant impact on employee performance. Leadership styles have a significant impact on employee performance. Motivation and leadership styles simultaneously have a significant influence on employee performance. Seeing these results it can be said that the independent variables are positive and significant effect on employee performance.